On the propagation of sonic waves in a dissociating gas - Sharma V.D.; Shyam R. (My University, 2025)
The effects of non-equilibrium dissociation and that of wave front curvature on the propagation of sonic waves and their consequent formation into shock waves are examined. Special attention is paid to waves of plane, cylindrical and spherical geometry propagating into regions of weak equilibrium or strong equilibrium. It is found that a state of strong equilibrium has a stabilizing influence in that not all compression waves will grow into shock waves. Further, it is interesting to note that in a weak equilibrium state, all compression waves, no matter how weak initially, always end up into a shock whereas all expansion waves decay but not completely unlike the situation that occurs in a strong equilibrium state. © 1979 with the authors.